2020
DOI: 10.3390/ijerph17197346
|View full text |Cite
|
Sign up to set email alerts
|

“We Just Take Care of Each Other”: Navigating ‘Chosen Family’ in the Context of Health, Illness, and the Mutual Provision of Care amongst Queer and Transgender Young Adults

Abstract: “Chosen family”—families formed outside of biological or legal (bio-legal) bonds—is a signature of the queer experience. Therefore, we address the stakes of “chosen family” for queer and transgender (Q/T) young adults in terms of health, illness and the mutual provision of care. “Chosen family” is a refuge specifically generated by and for the queer experience, so we draw upon anthropological theory to explore questions of queer kinship in terms of care. We employ a phenomenological approach to semi-structured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…The development of affirming social support is protective of mental health. Social support can act as a buffer against the adverse mental health consequences of violence, stigma, and discrimination (Bockting et al., 2013 ), can assist in navigating health systems (Jackson Levin et al., 2020 ), and can contribute to psychological resilience in TGD people (Bariola et al., 2015; Başar and Öz, 2016 ). Diverse sources of social support, especially LGBTQ + peers and family, have been found to be associated with better mental health outcomes, well-being, and quality of life (Bariola et al., 2015; Başar et al., 2016 ; Kuper, Adams et al., 2018 ; Puckett et al., 2019 ).…”
Section: Chapter 18 Mental Healthmentioning
confidence: 99%
“…The development of affirming social support is protective of mental health. Social support can act as a buffer against the adverse mental health consequences of violence, stigma, and discrimination (Bockting et al., 2013 ), can assist in navigating health systems (Jackson Levin et al., 2020 ), and can contribute to psychological resilience in TGD people (Bariola et al., 2015; Başar and Öz, 2016 ). Diverse sources of social support, especially LGBTQ + peers and family, have been found to be associated with better mental health outcomes, well-being, and quality of life (Bariola et al., 2015; Başar et al., 2016 ; Kuper, Adams et al., 2018 ; Puckett et al., 2019 ).…”
Section: Chapter 18 Mental Healthmentioning
confidence: 99%
“…In response to ongoing family rejection and the myriad of stressors that transgender individuals face, chosen family and other forms of resilience can become a lifeline to promote psychological health. Numerous studies have examined the positive impact of community support and chosen family on transgender individuals (Barr et al, 2016; Jackson Levin et al, 2020; Kichler, 2022; Nuttbrock et al, 2015). For trans youth of color, in particular, connecting to a larger community and self-defining racial/ethnic and gender identities builds resilience against racism and antitrans violence (Singh, 2013).…”
Section: Defining Family Rejection Within Latinx Familiesmentioning
confidence: 99%
“…A chosen family is a group of people who are emotionally close to one another and consider each other family without any biological or legal bonds [ 35 ]. There is still a lack of data about this topic as it relates to pediatrics, but in a recent study conducted on an adult population, Levin et al reported the experience of Tish, a nonbinary person who identifies as pansexual who met a chosen family for the first time when as a teenager and no longer keeps a relationship with the biological family [ 36 ].…”
Section: Home and Familymentioning
confidence: 99%